SECURITY ANALYSIS OF ONE SOLUTION FOR SECURE PRIVATE DATA STORAGE IN A CLOUD - Ludmila Klimentievna Babenko; Alina Viktorovna Trepacheva (Безопасность информационных технологий, 2016)
The paper analyzes the security of one recently proposed secure cloud data base architecture. We present an attack on it binding the security of whole solution with the security of particular encryption schemes, used in it. We show this architecture is vulnerable and consequently the solution is unviable.